Penerapan Etos Kerja Islami dalam Meningkatkan Produktivitas Karyawan pada Bank Syariah Mandiri Kantor Cabang Parepare - Satar, Muhammad (Institut Agama Islam Negeri Parepare, 2021)
Superior human resources and have a good work ethic can be influenced from the educational background and work experience possessed by the individual because the work ethic cannot be separated from the quality of the human resources themselves. Increasing the quality of employees can be achieved if there is an even and quality education, accompanied by an increase and expansion of education, expertise and skills so that the activities and productivity of employees as economic actors increases. In daily life as Muslims, in addition to being ordered to worship, God commands to work. In the Qur'an and the Hadith it is clear about good work and how we obtain sustenance in a way that is acceptable to Allah SWT. Discipline is one of the important factors in improving the quality of the work ethic, therefore discipline in employees must be increased every day.